2018
DOI: 10.1111/ffe.12788
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulation studies on fatigue behavior of laminated glass having polyvinyl butyral and ethyl vinyl acetate interlayers

Abstract: Cyclic fatigue strength (CFS) of laminated glasses (LGs) with different interlayers and their different nominal thicknesses were compared. The effect of interlayer thickness, cyclic bending fatigue load, and interlayer type on CFS is clearly observed from this brief study. It was found that the LG‐PVB has comparatively lower CFS than LG‐EVA. There is an increment in CFS with an increment in critical interlayer thickness (significantly for an increment from 0.38 to 0.76 mm) in both LG‐EVA (prominent) and LG‐PVB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Explicit Dynamics Module in ANSYS 14.5 (transient analysis) was used for simulating the fatigue test. The properties of glass and PVB are taken from Vedrtnam and Pawar (Table ). The loading and boundary conditions were taken similar to the experimentation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Explicit Dynamics Module in ANSYS 14.5 (transient analysis) was used for simulating the fatigue test. The properties of glass and PVB are taken from Vedrtnam and Pawar (Table ). The loading and boundary conditions were taken similar to the experimentation.…”
Section: Methodsmentioning
confidence: 99%
“…The material properties of each layer were defined. The linear elastic material model is followed during simulation . The tetrahedron and fine mesh (number of nodes 25 872, number of elements 5966) was used; grid refinement study was conducted; however, insignificant changes were observed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aerospace industry, it is used in airplane windows, while for architectural purposes, it is used as glass panels for buildings. By using laminated glass, the safety, security, fire resistance, and sound attenuation properties can be enhanced [ 16 ]. Moreover, laminated glass can also resist high impacts such as bullets and blast loads, as well as being applicable for safety and security purposes such as protection against hurricanes and cyclones.…”
Section: Introductionmentioning
confidence: 99%
“…The flow around bluff bodies, vortex formation, mechanisms of flow separation, the behaviour of the wake, and fluid-structure interactions are widely discussed. 1 The flow around bluff bodies of cylindrical shape has been studied considerably owing to its engineering importance in designing structures, acoustic emission dynamics, and fluid flow-induced vibration. [2][3][4][5][6][7][8][9] The bridge constructions, ad hoc defence structures, offshore platforms, tall buildings, heat exchangers, electrical transmission lines could break due to the vibration and oscillatory force; therefore, analysis of cylinder wake is significant.…”
Section: Introductionmentioning
confidence: 99%